Soil carbon sequestration for climate change mitigation: Mineralization kinetics of organic inputs as an overlooked limitation. (16th February 2022) - Berthelin, Jacques; Laba, Magdeline; Lemaire, Gilles; Powlson, David; Tessier, Daniel; Wander, Michelle; Baveye, Philippe C.
Abstract: Over the last few years, the question of whether soil carbon sequestration could contribute significantly to climate change mitigation has been the object of numerous debates. All of these debates so far appear to have entirely overlooked a crucial aspect of the question. It concerns the short‐term mineralization kinetics of fresh organic matter added to soils, which is occasionally alluded to in the literature, but is almost always subsumed in a broader modelling context. In the present article, we first summarise what is currently known about the kinetics of mineralization of plant residues added to soils, and about its modelling in the long run. We then argue that in the short run, this microbially‐mediated process has important practical consequences that cannot be ignored. Specifically, since at least 90% of plant residues added to soils to increase their carbon content over the long term are mineralized relatively rapidly and are released as CO2 to the atmosphere, farmers would have to apply to their fields 10 times more organic carbon annually than what they would eventually expect to sequester. Over time, because of a well‐known sink saturation effect, the multiplier may even rise significantly above 10, up to a point when no net carbon sequestration takes place any longer. The requirement to add many times more carbon than what one aims to sequester makes it practically impossible to add sufficient amounts of crop residues to soils to have a lasting, non‐negligible effect on climate change. Nevertheless, there is no doubt that raising the organic matter content of soils is desirable for other reasons, in particular guaranteeing that soils will be able to keep fulfilling essential functions and services in spite of fast‐changing environmental conditions. Highlights: Attempts to promote soil carbon sequestration to mitigate climate change have so far ignored the short‐term effects of the mineralization of plant residues added to soils. Only about 10%, at most, of added plan residues remain in soils after mineralization by soil organisms. To have a significant effect on climate change, farmers would need to add impractically large amounts of plant residues, requiring unrealistic nitrogen inputs. Therefore, rather than as a mitigation strategy, farmers should aim to increase the carbon content of soils to make them resilient to climate change.